Antihypercholesterolemic Potential of Ethanolic Leaf Extracts of Santalum album L., Calotropis gigantea, Ziziphus spina-christi L. - Khoirul Ngibad; Elis Dwi Nuryani; Tarisatus Syahlum Mukarromah; Nurisma Fadhila (Jurnal Penelitian Pendidikan IPA, 2025)
Hyperlipidemia, especially elevated Low-Density Lipoprotein (LDL) cholesterol, is a global health problem that increases the risk of cardiovascular disease. Conventional treatment with statins is effective, but it often causes side effects. This study aims to evaluate the potential of sandalwood (Santalum album L.) leaf, biduri (Calotropis gigantea) leaf, and arabic bidara (Ziziphus spina-christi L.) leaf as an antihypercholesterolemia agent using ethanol extract to lower cholesterol levels in mice.  Extraction is carried out through maceration with 96% ethanol for 3 x 24 hours, then evaporated to produce a thick extract.  The samples used in the antihyperocholesterolterol test were extracts of Santalum album L., Calotropis gigantea, and Ziziphus spina-christi L. Six groups, six mice each, consisted of: negative control (I), positive control (II), simvastatin drug control (III), and three test dose groups (IV: 3.5 mg/20 g BW, V: 7 mg/20 g BW, VI: 14 mg/20 g BW). Cholesterol levels were measured by the Point of Care Testing (POCT) Method using a cholesterol strip test after a blood draw.  The results showed that simvastatin can lower cholesterol by 59 mg/dl. Moreover, Santalum album L. leaf extracts provided the most significant reduction in cholesterol (33 mg/dl), followed by Ziziphus spina-christi L. (31 mg/dl) and Calotropis gigantea (28 mg/dl).  Although simvastatin showed a greater decrease, the plant extract still exerted significant effects as an alternative to antihypercholesterolemia therapy. This decrease in cholesterol is related to the content of active compounds, such as flavonoids and phenolics, that reduce LDL oxidation. These findings suggest that Santalum album L. has promising potential as an herbal antihypercholesterolemic agent